2019
DOI: 10.3389/fnins.2019.00622
|View full text |Cite
|
Sign up to set email alerts
|

Median Nerve Stimulation Based BCI: A New Approach to Detect Intraoperative Awareness During General Anesthesia

Abstract: Hundreds of millions of general anesthesia are performed each year on patients all over the world. Among these patients, 0.1–0.2% are victims of Accidental Awareness during General Anesthesia (AAGA), i.e., an unexpected awakening during a surgical procedure under general anesthesia. Although anesthesiologists try to closely monitor patients using various techniques to prevent this terrifying phenomenon, there is currently no efficient solution to accurately detect its occurrence. We propose the conception of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…We chose the 750 milliseconds of delay according to the reaction time of an average person, in order to stimulate during the ERD corresponding to the start of the imagination. A previous study confirmed that a MNS during the MI would not inhibit the ERD produced by this MI [20].…”
Section: B Experimental Taskssupporting
confidence: 58%
See 3 more Smart Citations
“…We chose the 750 milliseconds of delay according to the reaction time of an average person, in order to stimulate during the ERD corresponding to the start of the imagination. A previous study confirmed that a MNS during the MI would not inhibit the ERD produced by this MI [20].…”
Section: B Experimental Taskssupporting
confidence: 58%
“…Nevertheless, detecting MI, especially asynchronously, is not a trivial task for current MI-based BCI. To answer this issue, we showed in a previous study that a BCI based on the median nerve stimulation (MNS) is a promising approach to detect AAGA without any trigger and with a higher performance [20]. Indeed, our results indicated that a MI significantly modulates the ERDs and ERSs previously generated by a MNS and also that classification based on MNS is more efficient than conventional classification based on MI versus rest.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, a study has shown that the BIS protocol was less useful in preventing awareness than end-tidal anesthetic-agent concentration (9). Moreover, innovative techniques, such as passive brain-computer interface (BCI) based on an intention of movement may provide a foundation that would allow to detect awareness (22).…”
Section: Discussionmentioning
confidence: 99%